Resolva a expressão 2⁶-{15-[ 9- ✓16 + ( 4²-3.5) + ✓36 ] + 3⁰} = * Quero cálculos e não achei o sinal de raiz Quadrada , aí coloquei esse ✓
Soluções para a tarefa
Respondido por
1
Resposta:
60
Explicação passo-a-passo:
2⁶-{15-[ 9- ✓16 + ( 4²-3.5) + ✓36 ] + 3⁰} =
2⁶-{15-[ 9- ✓16 + ( 16-3.5) + ✓36 ] + 3⁰} =
2⁶-{15-[ 9- ✓16 + ( 16-15) + ✓36 ] + 3⁰} =
2⁶-{15-[ 9- ✓16 + 1 + ✓36 ] + 3⁰} =
2⁶-{15-[ 9- 4 + 1 + 6 ] + 3⁰} =
2⁶-{15-[ 5+7 ] + 3⁰} =
2⁶-{15- 12 + 3⁰} =
2⁶-{15- 12+ 1} =
2⁶- 4 =
64-4=
60
mariadix87:
Valeuuuu < 3
Perguntas interessantes
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Espanhol,
10 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás